Women in the Digital Workplace: Gendered Challenges and Strategies for Work-Family Balance - Widiastiani, Nindry Sulistya (Advanced Studies on Socio-Economy Development, 2025)
Family responsibilities can impact workers’ employment relationships. These circumstances may lead to conflicts of interest between the dualities of working obligations and family duties. Workers might face discrimination, lower wages, delayed promotions, or other adverse outcomes because their employers perceive their responsibilities as secondary. Such challenges can affect all workers, particularly women, who are traditionally seen as the primary caregivers in the family. Employment relations are undergoing a shift in how workers carry out their duties. The emergence of working activities includes using digital platforms and alternatively creating working systems. This Digital Workplace trend involves completing tasks on digital platforms such as email, social media, or cloud systems. With this shift, workers can no longer attend the office in person. This research posits that the emergence of the digital workplace addresses cultural roles within families, especially with flexible working hours and informal work settings. On the other hand, the stakeholders may need to address several issues, including the uncertainty surrounding labor protections, encompassing workplace exploitation and fairness concerns. Therefore, this article argues the condition of women in the digital workplace, specifically by the lack of regulations that might have insights to recognize the value of women’s roles in the family, particularly by the uncertainty of digital platforms that change the landscape of the working system. Keywords: Digital Workplace, Family, Labour Law, Women, Workers